Impact of baseline conduction abnormalities on outcomes after transcatheter aortic valve replacement with SAPIEN‐3. Issue 1 (3rd October 2020) - Sammour, Yasser; Sato, Kimi; Kumar, Arnav; Gajulapalli, Rama Dilip; Lak, Hassan; Chawla, Sanchit; Banerjee, Kinjal; Kaur, Manpreet; Patel, Jay; Incognito, Cameron; Svensson, Lars; Popovic, Zoran; et al.
Abstract: Background: Baseline conduction abnormalities are known risk factors for permanent pacemaker (PPM) implantation after transcatheter aortic valve replacement (TAVR). We sought to determine the impact of baseline right bundle branch block (RBBB), left bundle branch block (LBBB), left anterior hemiblock (LAHB), first‐degree atrioventricular block (AVB) and atrial fibrillation/flutter (AF) on TAVR outcomes. Methods: Consecutive patients who underwent transfemoral TAVR with SAPIEN‐3 (S3) were included. We excluded patients with prior PPM, nontransfemoral access or valve‐in‐valve. Results: Among 886 patients, baseline RBBB was seen in 15.9%, LBBB in 6.3%, LAHB in 6.2%, first‐degree AVB in 26.3% and AF in 37.5%. The rate of 30‐day PPM was 10.1%. Baseline RBBB (OR 4.005; 95% CI 2.386–6.723; p  < .001) and first‐degree AVB (OR 1.847; 95% CI 1.133–3.009; p  = .014) were independent predictors of 30 day PPM. LAHB also resulted in higher PPM rates but only in unadjusted analysis (21.8% vs. 9.4%; p  = .003). Baseline LBBB and AF were associated with lower left ventricular ejection fraction (LVEF) at both baseline and 1 year after TAVR. However, Δ LVEF over time were noted to be similar with baseline LBBB (1.8% vs. 1.4%; p  = .809) and AF (1.1% vs. 1.7%; p  = .458). Moreover, baseline AF was also associated with higher stroke/transient ischemic attack (TIA) at 1 year (4.4% vs. 1.8%; p  = .019), 1‐year major adverse cardiac and cerebrovascular events (MACCE) (19.5% vs. 13.3%; p  = .012) and 2 year mortality (23.5% vs. 15.2%; p  = .016). None of the other baseline conduction defects affected long‐term mortality or MACCE. Conclusion: In our S3 TAVR population, baseline RBBB and first‐degree AVB predicted higher PPM risk. Prior LBBB and AF were associated with lower LVEF at both baseline and 1 year. Lastly, preexisting AF was associated with higher rates of mortality, stroke/TIA, and MACCE. Abstract : Central illustration. Impact of baseline conduction abnormalities on short‐ and long‐term clinical outcomes after TAVR using balloon‐expandable SAPIEN‐3 valve. (Abbreviations: AF, atrial fibrillation/flutter; AVB, first‐degree atrioventricular block; LAHB, left anterior hemiblock; LBBB, left bundle branch block; LVEF, left ventricular ejection fraction; MACCE, major adverse cardiac and cerebrovascular events; PPM, permanent pacemaker; RBBB, right bundle branch block).